2000
DOI: 10.1103/physrevd.62.087304
|View full text |Cite
|
Sign up to set email alerts
|

A small universe after all?

Abstract: The cosmic microwave background radiation allows us to measure both the geometry and topology of the universe. It has been argued that the COBE-DMR data already rule out models that are multiply connected on scales smaller than the particle horizon. Here we show the opposite is true: compact (small) hyperbolic universes are favoured over their infinite counterparts. For a density parameter of Omega_o=0.3, the compact models are a better fit to COBE-DMR (relative likelihood ~20) and the large-scale structure da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 22 publications
3
66
0
Order By: Relevance
“…In order to check this, a similar analysis has been carried out for deformed toroidal models whose fundamental cell is described by a rectangular box with sides L 1 = L 2 and L 3 . As shown in figure 6, the "pancake" type models ( In the previous literature, it has also been argued that an increase in the best-fit normalization constant is related to the large-angle suppression owing to the finite size of the spatial section [12]. From our analyses, it is found that inclusion of off-diagonal term can also give a comparable increase in the best-fit normalization constant as well.…”
Section: Fig 5 the Contribution Of Off-diagonal Elements For Cubic supporting
confidence: 72%
See 1 more Smart Citation
“…In order to check this, a similar analysis has been carried out for deformed toroidal models whose fundamental cell is described by a rectangular box with sides L 1 = L 2 and L 3 . As shown in figure 6, the "pancake" type models ( In the previous literature, it has also been argued that an increase in the best-fit normalization constant is related to the large-angle suppression owing to the finite size of the spatial section [12]. From our analyses, it is found that inclusion of off-diagonal term can also give a comparable increase in the best-fit normalization constant as well.…”
Section: Fig 5 the Contribution Of Off-diagonal Elements For Cubic supporting
confidence: 72%
“…However, for low matter density models Ω 0 < 1, constraints on the size of the spatial section are less stringent, since the bulk of large-angle temperature fluctuations can be produced in the curvature or Λ dominant era, leading to less stringent suppression in the large-angle power [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Should we be able to detect circles if the power spectrum cutoff is due to the size of the largest mode being $ 1= 0 ? While there is no rigorous theorem relating the size of the largest mode to the diameter of the fundamental domain, D, analysis of both negatively curved (Cornish & Spergel 2000) and positively curved (Lehoucq et al 2002) topologies suggest that D $ ð0:6 1Þ . Thus, if the '' peak '' in the power spectrum at ' $ 5 corresponds to the largest mode in the domain, we should be able to detect a pattern of circles in the sky.…”
Section: Intriguing Discrepanciesmentioning
confidence: 99%
“…Recent works [13][14][15][16] have shown that the angular power spectrum C l is completely consistent with the COBE-DMR data for some compact hyperbolic models which are incompatible with the previous analyses [17]. Because the angular sizes of fluctuations produced at the late epoch are large compared to those on the last scattering for flat or hyperbolic geometry, we expect that the constraints for compact flat models with low-matter-density can be also significantly loosened.…”
Section: Introductionmentioning
confidence: 64%